Blackwater biomethane recovery using a thermophilic upflow anaerobic sludge blanket reactor: Impacts of effluent recirculation on reactor performance. (15th November 2020) - Zhang, Lei; Guo, Bing; Mou, Anqi; Li, Ran; Liu, Yang
Abstract: Thermophilic anaerobic digestion is a promising process for high-solid blackwater (BW) treatment due to improved hydrolysis rates, high methanogenesis efficiency, and pathogen removal, when compared with mesophilic treatment. In the present work, the effects of effluent recirculation ( i.e., mixing) on thermophilic blackwater treatment were studied. A laboratory-scale thermophilic upflow anaerobic sludge blanket reactor was operated with and without effluent recirculation. The methanogenesis efficiency of the BW treatment increased from 45.0 ± 2.9% when effluent recirculation was applied to 56.7 ± 5.5% without effluent recirculation. Without effluent recirculation, the COD accumulation in the bioreactor was reduced from 17.2 to 3.8% and the effluent volatile fatty acids (VFA) concentration was reduced from 0.64 ± 0.18 to 0.15 ± 0.10 g/L. Further, both acetoclastic and hydrogenotrophic methanogenic activity increased from 101.3 ± 10.8 and 93.9 ± 6.1 to 120.4 ± 9.4 and 118.2 ± 13.2 mg CH4 -COD/(gVSS⋅d), respectively, after effluent recirculation was discontinued. The predominant methanogens changed from Methanothermobacter (67%) with effluent recirculation to Methanosarcina (62%) without effluent recirculation. As compared to the effluent recirculation conditions, the enhanced biomethane recovery and treatment performance without effluent recirculation can be attributed to the close proximity of bacteria and archaea groups and the reduced VFA accumulation. Predicted functional gene comparison showed higher prevalence of function for intermediate metabolite transportation (transporters, ATP-binding cassette (ABC) transporters, and two-component system) after discontinuing effluent circulation, which contributed to improved syntrophic propionate oxidation and syntrophic acetate oxidization and enhanced hydrogenotrophic methanogenesis. Highlights: Methane yield increased from 45.0 to 56.7% as effluent recirculation discontinued. Effluent VFA concentration reduced from 0.64 to 0.15 g/L without recirculation. Predominant methanogens changed to Methanosarcina (62%) as recirculation stopped. Intermediate metabolite transportation showed higher activity without recirculation.